Diagnostic and Prognostic Accuracy of Aortic Valve Calcium Scoring in Patients With Moderate-to-Severe Aortic Stenosis - Boulif, Jamila; Slimani, Alisson; Lazam, Siham; de Meester, Christophe; Piérard, Sophie; Pasquet, Agnès; Pouleur, Anne-Catherine; Vancraeynest, David; El Khoury, Gébrine; de Kerchove, Laurent; Gerber, Bernhard L.; Vanoverschelde, Jean-Louis (Frontiers in Cardiovascular Medicine, 2021)
Background. Assessing the true severity of aortic stenosis (AS) remains a challenge, particularly when echocardiography yields discordant results. Recent European and American guidelines recommend measuring aortic valve calcium (AVC) by multidetector row computed tomography (MDCT) to improve this assessment. Aim. To define, using a standardized MDCT scanning protocol, the optimal AVC load criteria for truly severe AS in patients with concordant echocardiographic findings, to establish the ability of these criteria to predict clinical outcomes, and to investigate their ability to delineate truly severe AS in patients with discordant echocardiographic AS grading. Methods and results. 266 patients with moderate-to-severe AS and normal LVEF prospectively underwent MDCT and Doppler-echocardiography to assess AS severity. In patients with concordant AS grading, ROC analysis identified optimal cut-off values for diagnosing severe AS using different AVC load criteria. In these patients, 4-year event-free survival was better with low AVC load (60-63%) by these criteria than with high AVC load (23-26%, log rank p<0.001). Patients with discordant AS grading had higher AVC load than those with moderate AS but lower AVC load than those with severe high-gradient AS. Between 36% and 55% of patients with severe LG-AS met AVC load criteria for severe AS. Although AVC load predicted outcome in these patients as well, its prognostic impact was less than in patients with concordant AS grading. Conclusions. Assessment of AVC load accurately identifies truly severe AS and provides powerful prognostic information. Our data further indicate that patients with discordant AS grading consist in a heterogenous group, as evidenced by their large range of AVC load. MDCT allows to differentiate between truly severe and pseudo-severe AS in this population as well, although the prognostic implications thereof are less pronounced than in patients with concordant AS grading.